An intimate theater - Borges, Paulo César Balardim (2024)
The text presents issue no. 30 of Móin-Móin -Journal of Studies on Animated Forms of Theatre, with the theme "35 years of Lambe-Lambe theater in Brazil," its composition context, the questions that prompted the authors, and an invitation to read the published articles.